(untitled) (The Pakistan Development Review, 2021)
In their book entitled Tax Reforms in Pakistan: Historic & Critical View authors Huzaima Bukhari and Ikramul Haq take up the important yet often under-researched topic of the taxation system in Pakistan. The book is a collection of various writings on the topic by the authors spanning over three decades and has been published online by the Pakistan Institute of Development Economics (PIDE).